2010
DOI: 10.1101/gr.108696.110
|View full text |Cite
|
Sign up to set email alerts
|

OPA1 links human mitochondrial genome maintenance to mtDNA replication and distribution

Abstract: Eukaryotic cells harbor a small multiploid mitochondrial genome, organized in nucleoids spread within the mitochondrial network. Maintenance and distribution of mitochondrial DNA (mtDNA) are essential for energy metabolism, mitochondrial lineage in primordial germ cells, and to prevent mtDNA instability, which leads to many debilitating human diseases. Mounting evidence suggests that the actors of the mitochondrial network dynamics, among which is the intramitochondrial dynamin OPA1, might be involved in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(148 citation statements)
references
References 43 publications
7
140
0
1
Order By: Relevance
“…Recently, mitochondrial fusion and fission factors have been shown to influence the organization of mtDNA nucleoids. 41,52,53 In the present study, we found that Mic60/Mitofilin has an important role in the maintaining of mtDNA nucleoid organization and function in mammals ( Figures 5B and 6a). Thus, an important question is how Mic60/Mitofilin regulates the distribution and size of mtDNA nucleoids?…”
Section: Discussionsupporting
confidence: 61%
“…Recently, mitochondrial fusion and fission factors have been shown to influence the organization of mtDNA nucleoids. 41,52,53 In the present study, we found that Mic60/Mitofilin has an important role in the maintaining of mtDNA nucleoid organization and function in mammals ( Figures 5B and 6a). Thus, an important question is how Mic60/Mitofilin regulates the distribution and size of mtDNA nucleoids?…”
Section: Discussionsupporting
confidence: 61%
“…In contrast to the previous gene products, which are directly linked to mtDNA replication and nucleotide balance, the OPA1 protein is a dynamin‐related GTPase involved in mitochondrial fusion, morphology, and apoptosis 22. The involvement of specific isoforms of OPA1 in mtDNA maintenance and nucleoid organization has been recently proposed 23. However, the mechanism linking specific OPA1 mutations to mtDNA maintenance and instability remains mostly unclear.…”
mentioning
confidence: 99%
“…54 Small hydrophobic peptide fragments from cleaved OPA1 may also contribute to mtDNA nucleoid attachment to the inner mitochondrial membrane, promoting mtDNA replication and distribution. 85 Disrupted mtDNA distribution, or cristae structure, is predicted to have secondary impacts on oxidative phosphorylation due to either inadequate mtDNA transcription or lack of inner membrane surface area for oxidative phosphorylation complex anchoring. It has been reported that decreased oxidative phosphorylation capacity in ADOA patients with OPA1 mutations correlates with relatively poor visual acuities, while related mutation carriers with normal vision appeared to have relatively preserved oxidative phosphorylation function.…”
Section: Mitochondrial Diseases and Optic Neuropathiesmentioning
confidence: 99%